IDENTIFICATION TYPE OF GAS BASED ON DISCHARGE TIME MEASURING IN LIGHT EMITTING DIODE SERIES - Prasetiyo, Bagus; Exaudi, Kemahyanto; Mahjud, Ichsan (Jurusan Teknik Elektro Politeknik Negeri Ujung Pandang, 2025)
Nowadays, gas or vapor detection to observe environment situation is very required in many fields. Spectrophotometer method is always used to analyze contain and gas concentrate based on the absorption intensity of light by the gas sample. This research used Light Emitting Diode (LED) series act as a transmitter and light receiver (detector). Above detector surface is layered by a chemical membrane that selective in to the type of gas according the polarization level. This vapor absorption in chemical membrane can cause shrinking the intensity of light that hit the detector. This light will be discarding the load in internal capacitor of the detector. Duration internal sudden discharge of the LED depends on light intensity that hit it. Detector LED series that layered by different chemical membrane is produce different an absorption phase that patterning different discharge time. In this experiment, alcoholic solution and gasoline are used as vapor samples. Identify types of gas using imitation nerve connection method to finding out every type of gas with 80% success.